2011
DOI: 10.1177/1741826711409171
|View full text |Cite
|
Sign up to set email alerts
|

Individual patient meta-analysis of exercise training effects on systemic brain natriuretic peptide expression in heart failure

Abstract: Exercise training has favourable effects on BNP, NT-pro-BNP, and peak VO(2) in heart failure patients and BNP/NT-pro-BNP changes were correlated with peak VO(2) changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
51
1
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(62 citation statements)
references
References 23 publications
7
51
1
3
Order By: Relevance
“…The low level of bias and significant improvement in both NTproBNP and the VE/VCO 2 slope associated with AEX is a relevant finding to help the management of patients with HF. One previous meta-analysis and one systematic review [28,78] found a positive effect of an exercise-based treatment on NTproBNP. Although recent studies have reported that NTproBNP is more prognostic in mild to severe HF patients [43], we evidenced this lack of information on this subgroup (mild to severe HF patients is not a subgroup-it is likely all patients with HF with mild, moderate, and severe HF-mild to severe HF encompasses all).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The low level of bias and significant improvement in both NTproBNP and the VE/VCO 2 slope associated with AEX is a relevant finding to help the management of patients with HF. One previous meta-analysis and one systematic review [28,78] found a positive effect of an exercise-based treatment on NTproBNP. Although recent studies have reported that NTproBNP is more prognostic in mild to severe HF patients [43], we evidenced this lack of information on this subgroup (mild to severe HF patients is not a subgroup-it is likely all patients with HF with mild, moderate, and severe HF-mild to severe HF encompasses all).…”
Section: Discussionmentioning
confidence: 97%
“…Evidence demonstrating that EX training attenuates pathological hypertrophy [26] and improves endothelial dysfunction has also been put forth [27] It is therefore reasonable to hypothesize that the improvement in endothelial function as a result of AEX training program will have a positive impact on BNP. There are a few systematic studies evaluating the impact of AEX on NTproBNP in HF patients, especially in those with a diagnosis of systolic heart failure [13,15,28].…”
Section: Introductionmentioning
confidence: 99%
“…76 Another mechanism of regulating sympathetic tone is through the actions of plasma adrenomodullin and atrio/brain-natriuretic-peptides which are tied closely to aerobic consumption. 80 These molecules attenuate BP by suppressing noradrenaline and endothelin-1, and improving endothelial responsiveness and function. 81,82 ET also protects against oxidative stress, leading to lower nitric oxide scavenging by oxidation and higher nitric oxide bioavailability which have anti-hypertensive effects.…”
Section: Effects Of Et On CV Physiologymentioning
confidence: 99%
“…A 2011 review by Smart [5] estimated the hospital-based exercise therapy treatment costs to prevent mortality in one systolic heart failure patient to be approximately US$60K per annum. A range of benefits are likely in patients with systolic heart failure undertaking exercise training [6][7][8][9][10][11][12][13][14]. Meta-analyses have shown exercise training to be beneficial in HFpEF patients in terms of improved cardio-respiratory fitness [15][16][17].…”
Section: Introductionmentioning
confidence: 99%